(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Like other branches of the national economy, tomato cultivation is being developed with the help of innovative technologies. Among the vegetable crops, the tomato fields are being expanded and updated. Particularly high-yielding and high-quality varieties of tomatoes ripening in different periods, as well as varieties resistant to pests and diseases, are grown. To achieve a solution to these problems, it is necessary to develop a system of scientifically based measures aimed at combating plant pests and various pathogens. As a result of pest damage in tomatoes in the greenhouse, the taste and product quality of the fruits are lost and the productivity is reduced. As a result, these lead to a sharp increase in the cost of production and negatively affect the profitability of farms.